"Why I stayed when others left": an appreciative inquiry of retention in the prevention of mother to child transmission of HIV in Takoradi Government Hospital, Ghana - Abraham, Susanna Aba (Department of Health and Rehabilitation Sciences, 2019)
Globally, great strides have been made in developing essential strategies and knowledge necessary to prevent vertical transmission of HIV. Retention in the Prevention of Mother to Child Transmission (PMTCT) programme is essential for the achievement of this aspiration. The study applied Mixed Method Sequential Explanatory Design to explore the factors that underscored the retention decisions of newly diagnosed HIV positive pregnant women. The study was set in the PMTCT programme in the Takoradi Government Hospital, Ghana, a lower middle income country. PMTCT records were retrospectively reviewed. Subsequently, the Appreciative Inquiry process using the 4Is terminology was applied to unearth the experiences and aspirations of mothers (n=12), midwives and Community health nurses (CHNs) (n=12) engaged in the programme. Ethical approval was granted by University of Cape Town Faculty of Health Sciences Human Ethics Research Committee and Ghana Health Service Ethics Review Committee. Retention rate at six weeks postpartum was 67.4%. Retention stories of women enrolled in the PMTCT programme reflected a life-enhancing experience in the face of a life-threatening diagnosis. Four themes were generated: Transitioning to the ‘new’ woman, Journeying with committed companions, Glimpses of triumph and Tying up the loose ends: A daring new path. The study highlighted development of hope in a seemingly hopeless situation, supportive network of family, healthcare professionals and religious leaders, and the commitment and companionship of the midwives and CHNs that culminated in the successes of the programme. ‘Healthy’ HIV-infected mothers and ‘exposed’ infants who tested negative to HIV at the end of the mother-infant pair’s journey in the PMTCT programme was evidence of the diligence of mothers, midwives and CHNs. A collaborative discussion resulted in the development of action plans to improve service delivery, enhance clients’ experiences and improve retention. The study recommends that PMTCT services should be structured to promote hope and empowerment for the clients through shared clients and healthcare professionals’ designed improvement programmes, instituting programmes that promote the emotional health of the health practitioners to sustain the programme, and promptly addressing health system challenges that contribute to disengagement.